Air pollution - Gay, Kathlyn (New York : F. Watts, 1991)
Examines the growing problem of air pollution, its effect on the ozone and stratosphere and what we can do to improve air quality. Also evaluates the protective legislative measures that international governments are introducing to address these issues.
Ill blows the wind -- Yellow smog, brown haze -- Acid rain -- Global warming -- Attack on the Ozone layer -- Poisons in the air -- Ultimate pollutant -- hazardous indoor air -- clean air--how do we get it? -- The buck stops here.
Includes index, glossary, source notes and a list of organizations to contact.
Bibliography p. : 133-144.
Book Report.
Wilson's Junior High School.
Wilson's Senior High School.
7-10.
Keywords: Air -- Pollution -- Juvenile literature; Air -- Pollution; Pollution; Air pollution; Pollution